Genetic identification of Fasciola hepatica by ITS-2 sequence of nuclear ribosomal DNA in Turkey - Erensoy, Ahmet; Kuk, Salih; Ozden, Mehmet (Springer, 2009)
The trematodes of the genus Fasciola are the common liver flukes of a range species of animals and have a global geographical distribution. They can generally be distinguished on the basic of their morphology. ITS-2 ribosomal DNA sequences have been used to characterize the liver flukes as a specific marker from different geographical regions which include F. hepatica, F. gigantica, and an intermediate Fasciola. To determine the phylogenetic location of F. hepatica of Turkey origin based on ITS-2 rDNA molecular data, adult F. hepatica trematodes were collected from the liver naturally infected sheep from different geographical locations in Turkey (Elazig, Malatya, Samsun). ITS-2 rDNA were cloned, sequenced, and compared with published sequences ITS-2 rDNA of other species of trematodes in the family Fasciolidae using the GenBank Blast program. The only one ITS-2 sequence had defined for the examined Turkish F. hepatica samples. The phylogenetic trees constructed based upon the ITS-2 sequences from Turkey by multiple tree-building methods in MEGA revealed a close relationship with isolates of F. hepatica, F. gigantica, and Fasciola sp. The present study is the first demonstration of the existence of F. hepatica in sheep in Turkey by the genetic approach using ITS-2 rDNA as genetic marker.
Keywords: Internal Transcribed Spacer; Liver Fluke; Geographical Localities; Molecular Evidence; Cathepsin L1; F-Gigantica; Digenea; Differentiation; Samples; Echinostoma